Multiple Levels of Immunological Memory and Their Association with Vaccination - Zsófia Bugya; József Prechl; Tibor Szénási; Éva Nemes; Attila Bácsi; Gábor Koncz (Vaccines, 2021)
Immunological memory is divided into many levels to counteract the provocations of diverse and ever-changing infections. Fast functions of effector memory and the superposition of both quantitatively and qualitatively plastic anticipatory memory responses together form the walls of protection against pathogens. Here we provide an overview of the role of different B and T cell subsets and their interplay, the parallel and independent functions of the B1, marginal zone B cells, T-independent- and T-dependent B cell responses, as well as functions of central and effector memory T cells, tissue-resident and follicular helper T cells in the memory responses. Age-related limitations in the immunological memory of these cell types in neonates and the elderly are also discussed. We review how certain aspects of immunological memory and the interactions of components can affect the efficacy of vaccines, in order to link our knowledge of immunological memory with the practical application of vaccination.